Effects of extracellular polymeric substances on silver nanoparticle bioaccumulation and toxicity to Triticum aestivum L. (October 2021) - Fu, Qing-Long; Zhong, Chun-Jie; Qing, Ting; Du, Zi-Yan; Li, Cheng-Cheng-; Fei, Jun-Jie; Peijnenburg, Willie J.G.M.
Abstract: The potential effects of extracellular polymeric substances (EPS) on the behavior and toxicity of silver nanoparticle (Ag-NPs) and silver sulfide nanoparticle (Ag2 S-NPs) remains ambiguous. The interaction of EPS from Bacillus subtilis with Ag2 S-NPs, metallic Ag-NPs, or ionic Ag, and the associated plant safety had been examined in this study. The biological impacts of Ag-NPs and Ag2 S-NPs were Ag form-dependent and highly influenced by microbial EPS. Compared with metallic Ag-NPs, Ag2 S-NPs exert inert biological impacts, as revealed by 3.44 times lower Ag bioaccumulation in wheat ( Triticum aestivum L.) seedlings and nearly reduce plant biomass when wheat was subjected to 1.0 mg-Ag L −1 of Ag-NPs and Ag2 S-NPs with the transfer factors of 151.56–930.87 vs. 12.52–131.81, respectively. These observations were coincident with the low dissolved Ag ([Ag]diss ) in the Ag2 S-NPs treatment than the Ag-NPs treatment (114.0 vs. 0.0791, μg L −1 ). Compared with the enhanced toxicity of Ag2 S-NPs to wheat, Bacillus subtilis EPS significantly alleviate the phytotoxicity of Ag-NPs, as revealed by the relative root elongation (7.15–45.40% decrease vs. 2.39–11.75% increase), and malondialdehyde (1.47–83.22% increase vs. 8.57–25.25% decrease) and H2 O2 (11.27–71.78% increase vs. 5.16–36.67% decrease) contents. These constrasting plant responses of B. subtilis EPS are mainly caused by their complexation property with toxic Ag + and nutrient elements for wheat stressed by Ag-NPs and Ag2 S-NPs, respectively. Our findings highlight the importance of rhizospheric EPS in affecting the biogeochemistry and ecotoxicity of metal nanoparticles including Ag-NPs and Ag2 S-NPs in agricultural systems. Graphical abstract: Image 1 Highlights: EPS reduce the uptake of Ag in media with AgNO3, AgNPs and Ag2 S-NPs. EPS alleviate the toxicity of AgNO3 and AgNPs, but enhance the toxicity of Ag2 S-NPs. EPS affect the bioaccumulation and phytotoxicity of metal nanoparticles. Rhizospheric EPS is critical in affecting health safety of metal nanoparticles via food chains.